Clinical and paraclinical factors contributing to microglial activation in multiple sclerosis – A PET imaging study - Laaksonen, Sini (fi=Turun yliopisto|en=University of Turku|, 2026)
Multiple sclerosis (MS) is a chronic inflammatory and neurodegenerative autoimmune disease of the central nervous system (CNS). In the majority of patients, MS manifests as a relapsing-remitting (RR) disease, which may evolve over time into secondary progressive (SP) disease, leading to irreversible disability. The exact pathogenic mechanisms underlying disease progression are unknown. However, compartmentalized chronic inflammation, including activation of microglial cells, likely plays a central role. Neuropathological studies have demonstrated that activated microglia are present at the rims of chronic active lesions as well as diffusively in the normal-appearing white matter (NAWM). Microglial activation has been shown to correlate with disease severity and predicts disease progression. Positron emission tomography (PET) imaging using radioligands binding to translocator protein (TSPO) enables in vivo quantification of microglial activation in the brain, and TSPO-PET is considered a marker of inflammatory activity in MS. This thesis consists of three studies. Study I assessed, which demographic, clinical, and paraclinical MS disease-related parameters are associated with later TSPO-PET measurable microglial activation. Study II evaluated the effect of sex on [ 11C]-PK11195 binding in people with MS (pwMS) and in healthy individuals. Study III explored the usability of various imaging and serum biomarkers in predicting conversion to SPMS. In these studies, a higher number of WM lesions on diagnostic brain MRI, a higher immunoglobulin (IgG) index, and an early increase in the Expanded Disability Status Scale (EDSS) score were associated with increased microglial activation an average of 12 years later. Compared to women, [ 11C]-PK11195 binding was more prominent in both healthy men and male pwMS. Increased microglial activation, as quantified by TSPO-PET, elevated serum glial acidic fibrillary protein (GFAP) concentration, and thalamic atrophy predicted SPMS conversion. This thesis demonstrates an association between early clinical factors and later microglial activation that is detrimental to disease progression, and suggests that TSPO-PET, along with serum GFAP concentration and thalamic volume measurement, may be useful in assessing disease prognosis in pwMS.

Mikrogliasolujen aktiivisuuteen vaikuttavat tekijät MS-taudissa – PET-tutkimus Multippeliskleroosi eli MS-tauti on keskushermoston tulehduksellinen ja hermostoa rappeuttava autoimmuunisairaus. MS-tauti alkaa usein aaltomaisena tautimuotona ja voi edetä myöhemmin toissijaisesti eteneväksi MS-taudiksi (SPMS). Mikrogliasolujen aktivoitumisen on osoitettu liittyvän keskeisesti SPMS-taudissa nähtävään hermosolujen vaurioitumiseen. Neuropatologisissa tutkimuksissa aktivoituneita mikrogliasoluja on löydetty tulehduspesäkkeiden ympäriltä ja magneettikuvauksessa (MK) normaalilta näyttävästä valkeasta aivoaineesta. Mikrogliasolujen aktivoitumisen asteen on osoitettu korreloivan taudin vaikeusasteen ja ennustavan taudin etenemistä. Positroniemissiotomografialla (PET) translokaatioproteiiniin (TSPO) sitoutuvia radioaktiivisesti leimattuja merkkiaineita käyttäen voidaan tutkia aktivoituneita mikrogliasoluja aivoissa in vivo. Oletuksena on, että TSPO-PET-kuvauksella voidaan arvioida aivojen tulehdusreaktion voimakkuutta MS-taudissa. Väitöskirja koostuu kolmesta tutkimuksesta. Ensimmäisessä tutkimuksessa arvioitiin, mitkä tekijät MS-taudin diagnoosivaiheessa vaikuttavat myöhempään TSPO-PET-kuvauksella mitattavaan mikrogliasolujen aktiivisuuteen. Toisessa tutkimuksessa arvioitiin sukupuolen vaikutusta TSPO-molekyyliin sitoutuvan [ 11C]-PK11195 merkkiaineen sitoutumiseen terveillä ja MS-tautia sairastavilla. Kolmannessa tutkimuksessa selvitettiin, voidaanko erilaisia kuvantamis- ja verestä mitattavia biomarkkereita hyödyntää arvioitaessa SPMS-taudin riskiä. Tutkimuksissa suurempi valkean aineen muutosten määrä diagnostisessa MK:ssa, korkeampi selkäydinnesteen immunoglobuliini G (IgG) indeksi ja varhainen MS-taudin aiheuttama haitta liittyivät lisääntyneeseen mikrogliasolujen aktiivisuuteen keskimäärin 12 vuotta myöhemmin. Verrattuna naisiin, [ 11C]- PK11195 merkkiaineen sitoutuminen oli voimakkaampaa sekä terveillä että MS-tautia sairastavilla miehillä. Lisääntynyt TSPO-PET-kuvauksella todettu mikrogliasolujen aktiivisuus, korkeampi veren GFAP (glial fibrillary acidic protein) pitoisuus ja talamuksen pienempi koko ennustivat SPMS-taudin kehittymistä. Väitöskirja osoittaa varhaisten kliinisten tekijöiden yhteyden myöhempään mikrogliasolujen aktiivisuuteen. TSPO-PET kuvausta, GFAP pitoisuutta ja talamuksen tilavuutta voidaan käyttää arvioitaessa MS-taudin ennustetta.